A comparative analysis of milk sectors -- Nairobi, Kathmandu, Santa Cruz: opportunities for pro-poor policies - Anderson, S.; Tulachan, P.M.; Rushton, Jonathan; Staal, Steven J.; Herrero, Mario (Nottingham University Press, 2004)
This chapter presents the main findings of a set of comparative milk sector surveys carried out in Kathmandu (Nepal), Nairobi (Kenya), and Santa Cruz (Bolivia). The surveys assessed changes in demand, supply and marketing of milk and milk products over a ten to fifteen year period to 2001. This chapter considers the changes in demand and market share, the supply-side changes, the trading pathways, the policy framework, the growth in the sector and poverty reduction. Policy implications for pro-poor Development of the milk sector are discussed.